The hydrochemistry of Angwan Mallam and environs (PART OF KEFFI SHEET 208 NE) - Adama Baba; Olalekan Agboola Olowoyeye (Journal of Applied Sciences and Environmental Management)
The rock types in the area are migmatite, granodiorite, pophyritic granodiorite, and biotite gneiss intruded by mineral bearing pegmatite dyke. The structural trend of the rocks conforms to the general pan-African Orogeny deformation trending NE - SW. Structures like fault, vein, joint and foliations were observed during the field mapping. Eleven water samples were collected from surface water and wells of the study area for physio-chemical analysis. The result of the water analysis shows the major cations, anions, and heavy element: Mg+, Ca2+, Na+, K+, SO42-, NO3-, Cl-,, HCO3 - , and Fe, Cu, Pb. The pH, temperature, electrical conductivities, acidity, alkalinity, total dissolved solid, and turbidity were determined. The cation, anion, and heavy element are majorly derived from leaching of the surrounding rocks and human activities influence as the mining activities in some of the villages does not contaminate or pollute its water, soil and wellbeing of the people living in Agwan mallam. The findings will be a benefit to Environmental Impact Assessment of Agwa mallam as the water in the area meets the National Agency for Food, Drug Administration and Control, Draft for National Standard for Drinking water, and World Health Organization guideline. @JASEM